2019
DOI: 10.1111/bcpt.13370
|View full text |Cite
|
Sign up to set email alerts
|

A model to predict the risk of aspirin/non‐steroidal anti‐inflammatory drugs‐related upper gastrointestinal bleeding for the individual patient

Abstract: Upper gastrointestinal bleeding is a feared complication of using non‐steroidal anti‐inflammatory drugs (NSAIDs) or aspirin. Studies predicting the incidence rate for individuals with a given set of characteristics are lacking. The aim of this study was to develop a risk model to predict the incidence rate of upper gastrointestinal bleeding (UGIB) in users of aspirin/NSAID based on presence of well‐defined risk factors for the individual patient. Methods The model was developed from data from a case‐control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
1
9
2
Order By: Relevance
“…Their findings are in favor of the findings shown in a Danish study in which more than 60% of the patients with non-variceal bleed presented with UGIB. 19,20 Findings from our study was contradictory with the above-mentioned studies as in our findings only 13 (2.4%) patients used NSAID and 23 (4.3%) patients used antiplatelet. Therefore, in our study use of NSAID was not the common cause of UGIB.…”
Section: Discussioncontrasting
confidence: 96%
“…Their findings are in favor of the findings shown in a Danish study in which more than 60% of the patients with non-variceal bleed presented with UGIB. 19,20 Findings from our study was contradictory with the above-mentioned studies as in our findings only 13 (2.4%) patients used NSAID and 23 (4.3%) patients used antiplatelet. Therefore, in our study use of NSAID was not the common cause of UGIB.…”
Section: Discussioncontrasting
confidence: 96%
“…In one study, age, male sex, anaemia, aspirin and anticoagulants were identified as predictors, while GI history and cotreatment with corticosteroids and SSRIs were not 6 . In another study, age, history of GI bleeding or perforation, concomitant use of corticosteroids, SSRIs and antithrombotic agents, and male sex were identified 1 . In our study, concomitant PPI or H2RA treatment with NSAID reduced the risk of serious GI complications, whereas the use of rebamipide or Artemisia herb soft extract did not.…”
Section: Discussionmentioning
confidence: 99%
“…9 The side effects of NSAIDs therapy can be even more severe, namely the occurrence of gastrointestinal bleeding. [10][11][12][13] Pharmacognosy Journal, Vol 14, Issue 3, May-June, 2022 COX-1 is inhibited it results in tissue ischemia. The role of COX-2 is to improve wound healing and inhibit adherent leukocytes.…”
Section: Introductionmentioning
confidence: 99%